Current Concepts on Imaging Diagnosis of Rotator Cuff Disease - Chang, Eric Y.; Chung, Christine B. (Seminars in Musculoskeletal Radiology, 2014)
Rotator cuff disease is common and may be clinically silent or a cause of shoulder pain. Evaluation of the rotator cuff before and after surgery is challenging for the orthopedic surgeon, but the radiologist can make an accurate diagnosis and facilitate appropriate management. This article reviews the current concepts on imaging diagnosis of rotator cuff disease, beginning with a discussion of the complex anatomy of the rotator cuff, continuing into the normal and pathologic MR imaging appearances of the rotator cuff including tendinosis and tearing, and concluding with a review of the postoperative cuff after various surgical repair techniques.
Keywords: rotator cuff disease; rotator cuff anatomy; tendinosis; tendon tear; postoperative